2012
DOI: 10.1186/1748-7161-7-18
|View full text |Cite
|
Sign up to set email alerts
|

Scoliosis detection, patient characteristics, referral patterns and treatment in the absence of a screening program in Norway

Abstract: BackgroundEarly diagnosis of idiopathic scoliosis allows for observation and timely initiation of brace treatment in order to halt progression. School scoliosis screening programs were abolished in Norway in 1994 for lack of evidence that the programs improved outcome and for the costs involved. The consequences of this decision are discussed.ObjectivesTo describe the detection, patient characteristics, referral patterns and treatment of idiopathic scoliosis at a scoliosis clinic during the period 2003–2011, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 59 publications
3
52
0
5
Order By: Relevance
“…Previous studies reported that difference in ramus length and anterior nasal spine-menton angles showed a statistically significant correlation (p<0.05) to the difference of coracoid height, clavicular angle, radiographic shoulder height, and clavicle-rib intersection [19,20,29]. Class II division 1 malocclusion was a common malocclusion in idiopathic scoliosis subjects that had a significant effect on the condylar asymmetry index compared to other malocclusions [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that difference in ramus length and anterior nasal spine-menton angles showed a statistically significant correlation (p<0.05) to the difference of coracoid height, clavicular angle, radiographic shoulder height, and clavicle-rib intersection [19,20,29]. Class II division 1 malocclusion was a common malocclusion in idiopathic scoliosis subjects that had a significant effect on the condylar asymmetry index compared to other malocclusions [30].…”
Section: Discussionmentioning
confidence: 99%
“…Correction of the spinal deformity, achievement of a balanced posture, and preservation of spinal mobility are the primary goals of surgical treatment [16]. Surgery for AIS is indicated in patients with thoracic curves that are predicted to progress to greater than 45 to 50 degrees by the time of skeletal maturity [17,18]. Surgery for EOS is indicated in patients with coronal curves greater than 60 degrees with progression, and those patients with anticipated progression in which nonoperative treatments have either failed or are contraindicated [19].…”
Section: Discussionmentioning
confidence: 99%
“…The FBT was always used, and a specially trained nurse assisted in the screening. Sweden is the only Scandinavian country with an ongoing SSS [2,34] .…”
Section: Status Of Sss In the Worldmentioning
confidence: 99%
“…Adolescent idiopathic scoliosis (AIS) is a complex three dimensional developmental deformity of the spinal column and associated rib cage characterized by a lateral deviation and axial rotation [1,2,3] . The diagnostic criterion is a lateral curvature of the spine measuring at least 10° on an X-ray as determined by the Cobb method [4] .…”
Section: Introductionmentioning
confidence: 99%